Health status evaluation of shallow coral reefs in Cahuita and Manzanillo, Costa Rica - Araya-Vargas, Alexander (2017)
Sedimentation, increased tourism, coral diseases and high ocean temperatures have become a permanent threat to reef areas worldwide. The aim of the present study was to evaluate the health status of the shallow reefs in Cahuita and Manzanillo, Limon, Costa Rica. A database, including species of all colonial sessile cnidarians and their known diseases, was created for the studied area. Subsequently, 15 transects were surveyed along the coast in 1-3 m deep bands of 10 x 1 m following the AGRRA V5.4 protocol. Of the 27 species found, 21 were reported from Cahuita and 23 from Manzanillo. The shallow coral reefs’ health status in both sites was good in terms of diseases, bleaching and mortality due to their low incidence. Sessile cnidarians’ species composition, colonies’ sizes and coverage were dominated by massive and lobate scleractinians such as Pseudodiploria clivosa and Siderastrea siderea. Macroalgal coverage was low (below 20%) and mostly represented by brown algae. Sea urchins’ densities were also low (below 1 ind/m2 except for Echinometra viridis in Manzanillo) and they trend to continue decreasing as the years go by.